The Relationship Among Expectancy Belief, Course Satisfaction, Learning Effectiveness, and Continuance Intention in Online Courses of Vocational-Technical Teachers College Students - Ye, Jian-Hong; Lee, Yi-Sang; He, Zhen (Frontiers in Psychology, 2022)
Since the beginning of year 2020, when the whole world were undergoing the COVID-19 epidemic, all schools were lockout and classes were suspended until e-learning was rushed to be online for students to continue their learning, including the students in China. Although many studies had discussed the effectiveness of online learning from many different points of views, it still remained many uncertainties on the qualities of distance learning, especially when under the circumstances of rush and students’ involuntary learning. This paper attempted to determine whether students’ learning expectation reach the qualities of distance learning or not. In this paper, the snowball sampling method was adopted to have 356 students who studied at vocational-technical teachers’ college in Mainland China. Based on the expectation confirmation theory and its model, five hypotheses were proposed to construct a research model to determine relationship between student’s expectancy belief, satisfaction, learning effectiveness and continuous learning intention when facing the dilemma of classes suspended but learning continues, learning online during this ongoing pandemic. The results of this study showed that: 1. the expectancy value belief were positively related with theoretical course satisfaction, but negatively related with practical course satisfaction; 2. theoretical course satisfaction and practical course satisfaction were positively related with learning effectiveness; 3. learning effectiveness was positively related with continuance to learn. In addition, three factors influencing the most on the qualities of theoretical course were environmental interference such as surrounding noises, poor Internet connection, and poor absorption of learning contents respectively, while three factors influencing the most on the qualities of practical course were inaccessible to practice, poor absorption of learning content, and lack of practical materials respectively. Based on the results analyzed, this study suggested schools and teachers focused on how to improve the qualities and to reduce or prevent any disturbances to the class given to fulfill students’ class expectation first and then to ensure students’ learning effectiveness and intention to continuous learning.